Diaphragm Pacing as a Rehabilitative Tool for Patients With Pompe Disease Who Are Ventilator-Dependent: Case Series. Issue 5 (1st May 2016) - Smith, Barbara K.; Fuller, David D.; Martin, A. Daniel; Lottenberg, Lawrence; Islam, Saleem; Lawson, Lee Ann; Onders, Raymond P.; Byrne, Barry J.
Abstract : Background and Purpose: Pompe disease is an inherited disorder notable for severe, progressive ventilatory compromise. Although ventilatory failure has been attributed to myofiber dysfunction secondary to diaphragmatic glycogen accumulation, neural involvement of the phrenic motor system is also a prominent feature. Direct diaphragm pacing supplements respiratory function in other disorders of the phrenic motor system. Accordingly, it is hypothesized that augmented neuromuscular activity via diaphragm pacing would promote weaning from mechanical ventilation in patients with Pompe disease who are unresponsive to conventional, muscle-directed treatments. Case Description: Three patients with Pompe disease developed diaphragm paresis that resulted in chronic mechanical ventilation dependence. After preoperative inspiratory muscle strengthening exercises failed to improve function, fine-wire pacing electrodes were laparoscopically implanted into the diaphragm. Diaphragm conditioning was initiated the first postoperative week and consisted of gradual increases in stimulation parameters, lengthening of stimulation sessions, and ventilator weaning. Ventilation and intramuscular electromyographic activity were recorded periodically during conditioning to quantify diaphragm neuromuscular function. Outcomes: During paced breathing without mechanical ventilation, tidal volumes increased, and 2 patients were weaned from daytime ventilator dependence within the first 3 months of pacing, which has been sustained over the long-term. A third patient reduced reliance on daytime ventilation, but weaning was delayed by malacia of the large airways. In all patients, pacing appeared to facilitate spontaneous phrenic motor unit activity during independent breathing without ventilator or pacer support. Discussion: The findings are consistent with the view that diaphragm pacing has potential rehabilitative value to reduce reliance on mechanical ventilation in people with Pompe disease, but further study is needed. Diaphragm pacing represents a paradigm shift in the management of respiratory insufficiency for Pompe disease that warrants further controlled examination.